(untitled) (Journal of Environmental Science and Natural Resources, 2015)
An experiment was carried out at the research farm of Patuakhali Science and Technology University (PSTU) during the period from November 2010 to April 2011 to study on growth and yield performance of cowpea cv. BARI Falon-1 under different treatment of GA3 as foliar spray to investigate the responses and most optimum level of gibberelic acid regarding growth and yield of Falon that are suitable to cultivate in coastal region of Bangladesh. Among the GA3 treatments, 33.33 ppm GA3 produced significantly the tallest plant (61.07 cm), maximum leaves and branches plant1 (28.50 and 19.73, respectively), higher LAI (1.10) and higher TDM plant1 (81.95 g) comparatively than that of other GA3 levels while control had lower on the above characters. Growth characters such as CGR, RGR and NAR had also higher (0.99 and 1.65 gm2 day-1 for CGR, 0.43 and 0.72 gm2 day1 for RGR and 0.027 and 1.275 mg cm2 day1 for NAR) in 33.33 ppm GA3 at the stage between 30 to 60 DAS and 60 to 90 DAS, respectively Yield contributing characters Among other observation of yield and yield contributing characters, 33.33 ppm GA3 further registered the maximum pods plant1 (11.50), longest pod (17.05 cm), higher weight fresh (3.78 g) and dry pod (1.99 g), higher weight of 100seed (12.25), seed yield (18.57 g plant1 and 2986.72 kg ha1) and higher HI (22.45%). These results also showed that GA3 up to 33.33 ppm signifciantly developmend morphophysiological, growth, yield and yield contributing characters and thereafter all the data decreased due to its destructive effect of higher GA3 levels. So, considering the above observation it could be suggested that GA3 @ 33.3 ppm would be appropriate doses of GA3 for obtaining the better produciton of BARI Falon-1 under resion. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22196 J. Environ. Sci. & Natural Resources, 7(2): 7-12 2014